The Relationship of Mother's Education Level, Mother’s Knowledge, Family Income and Nutritional Status of Toddler in The Working Area Of The Weekombak Puskesmas, West Sumba District - Kii, Yuliana Ina; Laga Nur, Marselinus; Sahdan, Mustakim (Journal of Ageing And Family, 2022)
Nutritional status is the condition of the body as a result of food consumption and use of nutrients. Nutrition is also one of the assets in determining the quality of resources that can enhance physical growth and the development of human intelligence. Based on the health profile of Southwest Sumba Regency in 2019, namely in June, there were 278 cases of malnutrition among five children, while there were 939 cases of malnutrition. Weekombak Health Center is one of the health centers in West Wewewa District, Southwest Sumba Regency. Weekombak health center is one of the health centers that has nutritional status problems with a total of 95 cases. The purpose of this study was to analyze the relationship between mother's education level, mother's knowledge, family income and the nutritional status of toddlers in the working area of the Weekombak Health Center, Southwest Sumba Regency. The type of research used is survey research with a cross-sectional design. The location and time of this research is in the working area of the Weekombak Health Center, Southwest Sumba Regency, in July-August 2022. The sample used in this study was 95 toddlers. The data obtained were analyzed using chi-square with a significance level of α=0.005. The results showed that there were variables that had a relationship with the nutritional status of toddlers, namely mother's education (p-value = 0.000), mother's knowledge (p-value = 0.000), family income (p-value = 0.003), therefore, mothers Those who have children under five are expected to pay attention to the nutritional status of children under five and participate in the care of children under five. Keywords : related factors, nutritional status, toddlers